Nutrition Components of Dry Noodles From Substitution of Aloe vera Skin Extract and Maize’s Sprout Flour - Narsih; Agato (Current Nutrition & Food Science, 2019)
Background: The dried noodles produced from maize raw materials soaked for 24 hours were germinated for 36 hours and the Aloe vera skin extracted at 80°C for 60 minutes showed high nutrients, proving that this food product has functional properties. Objective: To check the quality of dry noodles produced from the combination of maize sprout flour and Aloe vera skin extract. Subject and Methods: The materials used were maize and Aloe vera skin. Maize was soaked for 24 hours and germinated for 36 hours and the Aloe vera skin was extracted at 80°C for 60 minutes. The maize sprouts obtained were then dried and floured. Then, Aloe vera skin extract was added, followed by other noodle-forming materials for further processing of dried noodles. The nutrient components were analyzed in the produced noodles. Results: The maize sprout flour had 11.35% protein, protein digestibility 84.84%, starch 37.63%, phytate compound 131.09 mg/g, organic compounds 11 mg/g, and functional compounds 22 mg/g, while the noodle product had elongation of 96.15%, swelling index of 19.64%, tensile strength of 2.01 Nmm, 18 organic acids compounds (lactate, oxalate, succinic, malic, mevalonic, p coumaric, ascorbate, ferulic, panthotenic, myristic, hexadecanoic, palmitic, α-linoleic, linoleic acid, oleic, stearate, isobehenate and folic) and 23 functional groups in the range 527.29 - 3354.74 cm-1. Conclusion: Dry noodles produced from Aloe vera skin extract and maize sprout flour have functional properties.
Keywords: organic acids compounds